Role of silymarin as antioxidant in clinical management of chronic liver diseases: a narrative review - Aghemo, Alessio; Alekseeva, Olga P.; Angelico, Francesco; Bakulin, Igor G.; Bakulina, Natalia V.; Bordin, Dmitry; Bueverov, Alexey O.; Drapkina, Oxana M.; Gillessen, Anton; Kagarmanova, Elvira M.; Korochanskaya, Natalia V.; Kucheryavii, U. A.; et al. (Annals of medicine (Helsinki), 2022)
Chronic liver disease (CLD), manifested as hepatic injury, is a major cause of global morbidity and mortality. CLD progresses to fibrosis, cirrhosis, and-ultimately-hepatocellular carcinoma (HCC) if left untreated. The different phenotypes of CLD based on their respective clinical features and causative agents include alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), metabolic-associated fatty liver disease (MAFLD), and drug-induced liver injury (DILI). The preferred treatment modality for CLD includes lifestyle modification and diet, along with limited pharmacological agents for symptomatic treatment. Moreover, oxidative stress (OS) is an important pathological mechanism underlying all CLD phenotypes; hence, the use of antioxidants to manage the disease is justified. Based on available clinical evidence, silymarin can be utilized as a hepatoprotective agent, given its potent antioxidant, antifibrotic, and anti-inflammatory properties. The role of silymarin in suppressing OS has been well established, and therefore silymarin is recommended for use in ALD and NAFLD in the guidelines approved by the Russian Medical Scientific Society of Therapists and the Gastroenterology Scientific Society of Russia. However, to discuss the positioning of the original silymarin in clinical guidelines and treatment protocols as a hepatoprotective agent for managing CLD concomitantly with other therapies, an expert panel of international and Russian medical professionals was convened on 11 November 2020. The panel reviewed approaches for the prevention and treatment of OS, existing guidelines for patient management for CLD, and available evidence on the effectiveness of silymarin in reducing OS, fibrosis, and hepatic inflammation and presented in the form of a narrative review. Key messages An expert panel of international and Russian medical professionals reviewed existing guidelines for ALD, NAFLD, MAFLD, and DILI to establish consensus recommendations that oxidative stress is the common pathophysiological mechanism underlying these conditions. The panel also discussed the positioning of original silymarin in clinical guidelines and treatment protocols as a hepatoprotective agent for managing CLD concomitantly with other therapies. The panel reviewed the effectiveness of 140 mg original silymarin three times a day in reducing oxidative stress in chronic liver diseases such as ALD, NAFLD, MAFLD, and DILI.